Adherence to methotrexate therapy among rheumatoid arthritis patients in Eastern India - Mukherjee, Dibyendu; Naiya, Suman; Chakraborty, Suvajit; Chakrabarty, Rahul D.; Patra, Sucharita (International Journal of Advances in Medicine, 2020)
Background: This study aims to identify adherence rate of methotrexate (MTX) therapy in rheumatoid arthritis (RA) patients of Eastern India and recognize factors contributing to treatment adherence in those patients. Methods: In this cross-sectional observational study, a total of 140 patients (17 males, 123 females; mean age 37.6±7.4 years) with pre-diagnosed RA attending the rheumatology outpatients clinic between February 2019 and January 2020 fulfilling the inclusion and exclusion criteria, were included. The patients were evaluated in terms of sociodemographic factors, clinical and medication details, disease activity score (DAS28-CRP) values and patient - doctor considerations that might contribute to treatment adherence. They filled out a series of standardised present questionnaires including the Morisky 8-item Medication Adherence Scale (MMAS-8). Data was analysed statistically and compounded. Results: Of the patients, 29 (20.7%) were adherent and 111 (79.3%) were non-adherent to medication with MTX. 65% were on MTX monotherapy and 35% on polytherapy with csDMARDs. 45.7% of the non-adherent forgot taking medication, 50.7% skipped during travel, 79.3% intentionally did not comply with strict regimen. The DAS28-CRP scores were much higher amongst non-adherent group and fewer reached remission as compared to adherent participants. Commonest reason for non-adherence being adverse drug reaction and financial constraints. Conclusions: This study showed a significantly higher adherence to MTX treatment compared to most previous studies. Adverse drug reactions, financial constraints, complex treatment regimen, long treatment duration, and frequent travel history significantly affect medication adherence in this patient population. Higher the adherence better the treatment response.